Sombras de la onorosa praeda: un exemplo virgiliano para un aula granadina - José María Anguita; Elizabeth R. Wright (Criticón, 2012)
This article combines the disciplinary perspectives of a Latinist (Anguita) and a Hispanist (Wright) to cast light on the Austrias Carmen, a two-book epic by Joannes Latinus (Juan Latino, 1517? - 1590?). The poet, a former slave of black-African origins who taught Latin in Granada, deployed allusive Latin hexameters to recount the victory of the Holy League navy—comprised of Spain, Venice and Rome— over the Ottoman Turks in the Battle of Lepanto (October 7, 1571). To illustrate the role of imitatio, the authors analyze the references to one of the most debated episodes in Vergil’s Aeneid, the raid of Nisus and Euryalus from Book 9, vv. 176-449. As well, they contextualize the epic with reference to the morisco uprising which devastated the poet’s home city in the half-decade before the naval battle.